A Multisystem Psycho-Biological Approach to the Understanding of Parental Dispositions. (3rd April 2019) - Senese, Vincenzo Paolo; Azhari, Atiqah; Cataldo, Ilaria
SYNOPSIS: Does work-family conflict influence parental behaviors and parenting-related emotional states? Through an experimental research approach, River and colleagues showed that work-family conflict influences both emotions and parental behaviors, but the effect is moderated by the quality of the intimate relationship. In this commentary, we offer an interpretation of the results congruent with the recent theoretical approaches that stress the need for a multisystem psycho-biological approach to studying the factors that regulate parenting behaviors. In this perspective, we provide complementary explanations of the observed results and suggest possible future directions for research on these topics.